Zero charge point analysis and infrared spectroscopy of an activated carbon from malt bagasse (Research, Society and Development, 2024)
When improperly disposed of, malt bagasse can cause damage to the environment, due to its high pollution load. Currently, this byproduct is mainly sold for the production of animal feed, as it has high nutritional value and can also be used for human nutrition, or, due to its high availability, studied as a precursor material for chemical processes, such as adsorption. The zero charge point is an important parameter to be determined, especially in activated carbons based on materials little studied for the purpose of use in adsorption processes, as it indicates the pH of the medium in which the surface of this material will have a neutral charge. From the pH of the medium, it becomes possible to know the types of compounds, which can be anionic or cationic, that will be preferentially adsorbed, due to the potential surface charge of the materials. When the pH of the medium is lower than the point of zero charge, the material to be positively charged and the negatively charged molecules will be better adsorbed. When the pH is higher than the point of zero charge, the charge will be negative and the preference will be for molecules with a positive charge. Another important analysis is the study and identification of the functional groups of materials, thus enabling electronic spectroscopy analysis in the infrared region. Through the spectra it is possible to visualize types of vibrations of atomic and structural groups. Therefore, the objective of this article is to present a work to evaluate the zero charge point and infrared spectroscopy of a coal obtained from the waste material of the brewing industry, malt bagasse.